Camellia oil lowering blood pressure in spontaneously hypertension rats. (July 2020) - Guo, Lina; Guo, Yiting; Wu, Ping; Lu, Feng; Zhu, Junsong; Ma, Haile; Chen, Yong; Zhang, Tao
Graphical abstract: Highlights: The main components of camellia oil were oleic acid and linoleic acid. Camellia oil markedly reduced systolic blood pressure of SHRs. Camellia oil significantly reduced ACE activities in local tissues. Camellia oil modulated the balance of vasoconstrictor and relaxing factors. Abstract: The purpose of this study was to investigate the antihypertensive effect of camellia oil in vivo and its potential ACE-pathway mechanism. The results showed that the contents of oleic acid and linoleic acid in camellia oil were 78.83% and 8.32%, respectively. In vivo experimental results exhibited that both low-dose and high-dose groups significantly reduced the systolic blood pressure (SBP) in acute and long-term administration experiments compared to the control group. Camellia oil with various dosages significantly reduced the angiotensin-converting enzyme (ACE) activities of tissues and the levels of endothelin, renin and angiotensin II in serum. Moreover, camellia oil performed a similar reduction level on SBP of spontaneously hypertension rats (SHRs) for both captopril and olive oil. Overall, camellia oil exert antihypertension effect by modulating the balance of endothelium-derived vasoconstrictor and relaxing factors in serum.